Answer:
g(x) = x + 2 ⇒ 3rd answer
Explanation:
* Lets revise the translation
- If the function f(x) translated horizontally to the right
by h units, then the new function g(x) = f(x - h)
- If the function f(x) translated horizontally to the left
by h units, then the new function g(x) = f(x + h)
* Lets solve the problem
∵ The parent function f(x) = x + 6
∵ f(x) is shifted four units to the right
- The translation of a function by h units to the right change the x in
the function by subtracting h from it
∴ The x in f(x) will change to (x - 4)
∴ The new function = (x - 4) + 6
- Simplify the function
∴ The new function = x + 2
∵ The new function is g(x)
∴ g(x) = x + 2